Seeing and Hearing God with the Psalms : the Prophetic Liturgy of the Second Temple in Jerusalem. - Jacques Tournay, Raymond (Library of Hebrew Bible/Old Testament studies., 1997)
This investigation into the prophetic dimension of the Psalms shows how the postexilic period and especially the world of the Chronicler around 300 BCE provide the main setting for the Psalms, even royal psalms. The Levitical singers of the Second Temple 'made up for the silence of the classical prophets': an idealized David, musician and prophet, is depicted as leader of the cultic prophets and of the entire inspired community. In this way theophanic descriptions and oracular material in the style of the classical prophets were developed and preserved through the Psalms.